Scapa Flow: An Important Reminder of the Dangers of Vanity and the Need for Alacrity in Naval Battles - Pasaribu, Nico Daniel; Prakoso, Lukman Yudho; Syahtaria, Ikhwan; Mussayyab, Said (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Today's world is faced with a complex and constantly changing geopolitical landscape. Tensions that occur in the world such as the South China Sea, Ukraine, the Middle East make many countries in the world wary, including Indonesia. Indonesia as the largest archipelagic country needs a sea defense strategy to safeguard its national interests. This research aims to benefit from the Scapa flow battle to strengthen Indonesia's sea defenses. This research uses the literature study method. The results showed that the strongest defense can be penetrated if not equipped with strategy and careful preparation. In conclusion: in addition to the strategic geographical location, it is necessary to pay attention to other factors such as layered defense systems, conducting patrols and tight guard around sea bases, the use of the latest technology to detect and intercept submarines, and good training for personnel.